Hubungan Kondisi Psikologis Anak Pra Operasi dengan Tingkat Kecemasan Orang Tua di Ruang Bedah RSUD Kabupaten Buleleng - Putu Ayu Masriani; Ni Gusti Ayu Lia Rusmayani; Tri Suryo Wibowo (Universitas Triatma Mulya, 2022)
Introduction: Children preoperative surgery can cause feelings of anxiety in parents. Children would also experience psychological changes and behavioral changes both before, during and after surgery. The study aimed to known of the relationship between the psychological condition of preoperative children and the level of anxiety of parents in operating room of RSUD Kabupaten Buleleng. Methods: The design of study by quantitative descriptive analyzed with cross sectional method. The sample of study was the parents and their children’s would surgery in operating room of RSUD Kabupaten Buleleng. Results: The psychological condition of preoperative children is 83% of people and 17% of people wits stable and very stable conditions. The anxiety of parents with normal conditions is 28% of people, 23% of people with mild anxiety, 49% of people with moderate anxiety and 3% of people with severe anxiety. The significant value of Chi Square Analyzed is 0.001 (sig. <0.05), so the were of the relationship between the psychological condition of preoperative children and the level of anxiety of parents in the operating room of RSUD Kabupaten Buleleng. The correlation analyzed give value of Person Correlation is 0.702. The were strength correlation between the psychological conditions of preoperative children and the level anxiety of parents in the operating room of RSUD Kabupaten Buleleng. Conclusion. The conclusion of study is the were of the relationship between the psychological condition of preoperative children and the level of anxiety of parents.